2D Nanoarchitectures for Sensing/Biosensing Applications - Muhammad Asif; Fei Xiao; Mani Govindasamy; Yimin Sun (Frontiers in Chemistry, 2022)
Graphical AbstractSchematic illustration of 2D materials based sensors for the detection of various analytes.